The Concept of Education and Learning in the Qur’an Based on Surah Al-‘Alaq : an Islamic Perspective on Knowledge Development - Amiruddin; Syaripah Aini (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
Education holds a fundamental position in Islam, as emphasized in the first revelation to Prophet Muhammad (PBUH), Surah Al-‘Alaq. This study aims to analyze the educational concepts presented in Surah Al-‘Alaq and their relevance to modern education. Using a library research method with a descriptive-analytical approach, the study interprets various primary sources, including Tafsir Ibn Kathir, Tafsir Al-Maraghi, and Tafsir Al-Misbah. The findings reveal that Surah Al-‘Alaq outlines key educational principles, such as the importance of reading and writing, lifelong learning, and ethical-spiritual foundations in education. The surah underscores the role of knowledge in human development and civilization, highlighting its transformative power. Moreover, the study finds that these principles remain highly relevant to contemporary education, particularly in strengthening literacy culture, integrating character education, and utilizing technology for learning. The study concludes that Surah Al-‘Alaq not only underscores the significance of knowledge but also provides guidance for a sustainable education system rooted in Islamic values. To ensure the holistic development of individuals and their contributions to society, Islamic education should reinforce the principles found in Surah Al-‘Alaq, fostering knowledgeable, ethical, and responsible learners.